Development, Optimization, and Characterization of Wet-Granulated Curcumin Nanostructured Lipid Carrier Tablets - Mantika Atiqah Baihaty; Gumilar Adhi Nugroho; Deni Rahmat; Faridah Faridah (Faculty of Pharmacy Universitas Pancasila, 2025)
Curcumin has been widely recognized for its broad therapeutic potential, including its emerging role as an antiviral agent. However, its clinical translation is limited by poor aqueous solubility, rapid metabolism, and low oral bioavailability. To address these challenges, nanostructured lipid carriers (NLCs) have been proposed as a promising delivery system to enhance curcumin stability and systemic availability. This study aimed to formulate curcumin-loaded NLCs, optimize their physicochemical characteristics, and develop an oral tablet dosage form using the wet granulation method with super-disintegrant variation. The optimized NLC formulation was prepared and subsequently freeze-dried prior to compression into tablets. Particle size, polydispersity index (PDI), zeta potential, morphology, entrapment efficiency (EE), and loading capacity (LC) were evaluated. Tablets were formulated using starch, croscarmellose sodium (2% and 3%), PVP, aerosil, and Avicel PH 102, followed by assessment of physical quality parameters including weight uniformity, hardness, friability, disintegration, and dissolution profile. The optimized NLCs exhibited desirable nanoscale characteristics, with particle size of 70.95 nm, PDI 0.379, zeta potential −23.9 mV, spherical morphology, EE 99.75%, and LC 9.93%. The resulting tablets were yellow, bitter, and odorless, with acceptable pharmacopeial quality. Weight and size uniformity were within limits, hardness was 3.81 kg/cm² and 4.38 kg/cm², friability 1.45% and 0.50%, and disintegration times 1.86 min and 1.28 min for 2% and 3% super-disintegrant, respectively. Dissolution profiles indicated 26.12% and 25.79% release within the test period. Curcumin can be successfully formulated into stable NLCs with excellent encapsulation efficiency and incorporated into wet-granulated tablets meeting pharmacopeial standards. The use of 3% croscarmellose sodium provided the most favorable disintegration profile, suggesting its potential as an optimized oral dosage form to improve curcumin delivery and bioavailability.